Neoproterozoic geodynamic evolution of easternmost Kalahari: Constraints from U-Pb-Hf-O zircon, Sm-Nd isotope and geochemical data from the Schirmacher Oasis, East Antarctica - Jacobs, Joachim; Mikhalsky, Evgeny; Henjes-Kunst, Friedhelm; Läufer, Andreas; Thomas, Robert J; Elburg, Marlina; Wang, Chengcheng; Estrada, Solveig; Skublov, S G (Precambrian Research, 2020)
Late Tonian (ca. 785–760 Ma) granodioritic to granitic orthogneisses of the Schirmacher Oasis region in Dronning Maud Land (DML), East Antarctica, are interpreted as recording an active continental margin setting at the periphery of Kalahari and Rodinia. The rocks probably represent exposures of a significant tectonic province hidden beneath the ice, the erosional remnants of which are recorded as detrital zircons in late Tonian-Cryogenian metasedimentary rocks throughout central and eastern DML, as well as in ice-rafted debris from recent sediments offshore Dronning Maud Land. The orthogneisses have single-stage Sm-Nd model ages of ca. 1.3–1.5 Ga and zircon Hf-signatures (εHft = +2 – +5), indistinguishable from the adjacent Grenville-age basement rocks of easternmost Kalahari. Their geochemistry suggests that they evolved in the late stages of a continental margin magmatic arc and possibly within a roll-back tectonic framework, suggestive of subduction of relatively old oceanic lithosphere. The eastern Kalahari continental arc is one of a number of continental arcs that characterize the western part of the fragmenting Rodinia and document the supercontinent “turning inside out” after its formation at ca. 1000 Ma and a period of relative tectonic quiescence between ca. 900 and 800 Ma. The rocks show an ultra-high temperature metamorphic overprint that was accompanied by syn-tectonic magmatism from ca. 650 to 600 Ma. The high temperature metamorphism is interpreted to relate to back-arc extension that also led to major anorthosite magmatism elsewhere, prior to continental collision in the region. The rocks lack the subsequent widespread high-grade metamorphic overprint at ca. 590–500 Ma which occurs in the adjacent regions due to Himalayan-style continental collision along the East African-Antarctic Orogen during Gondwana assembly.
Keywords: Dronning Maud Land; geokronologi; geologi

Two distinct Late Mesoproterozoic/Early Neoproterozoic basement provinces in central/eastern Dronning Maud Land, East Antarctica: The missing link, 15–21°E - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Kleinhanns, Ilka C; Henjes-Kunst, Friedhelm; Estrada, Solveig; Ruppel, Antonia S; Damaske, Detlef; Montero, Pilar; Bea, Fernando (Precambrian Research, 2015)
This article highlights the field geology, geochronology and geochemistry of an important and previously unstudied region between eastern (Sør Rondane Mountains) and central Dronning Maud Land (DML). The area allows the characterisation and ground-truthing of a large and mostly ice-covered area that is geophysically distinct and which was previously interpreted as a potentially older cratonic block south of a Late Neoproterozoic/Early Paleozoic (LN/EP) mobile belt, as exposed in the Sør Rondane Mts. (SRM). SHRIMP/SIMS zircon analyses of 20 samples together with new geochemistry indicate that the exposed basement consists of a ca. 1000–900Ma juvenile terrane that is very similar to the juvenile rocks of the SW-Terrane of the SRM, a characteristic gabbro–trondhjemite–tonalite–granite (GTTG) suite, with normalised trace element patterns typical for subduction-related magmas and mostly positive initial epsilon Nd values. The area shows strong LN/EP crustal reworking, migmatisation and melt production, including 560–530Ma A-type magmatism. Therefore, this area is very similar to the SW-Terrane and differs only in the degree of LN/EP reworking. We interpret the SW-Terrane of Sør Rondane as a mega-boudin sandwiched in between rheologically weaker portions of similar oceanic arc terranes. Therefore, the study area, and thereby the aeromagnetically distinct SE DML province does neither represent the foreland of a LN/EP mobile belt, nor a craton, as speculated based on geophysical data alone. Instead, a large Tonian Oceanic Arc Super Terrane (TOAST) with significant extent emerges. Its western limit is represented by the Forster Magnetic Anomaly, which represents a suture to the Grenville-age Maud Belt. East of the TOAST, the Rayner Complex is similar in age but otherwise distinctly different. The Rayner Complex has a much longer history of island arc accretions with continent–continent collision at ca. 950Ma and it has markedly more evolved crust. In contrast, the TOAST has a pronounced juvenile character without significant inheritance and lacks metamorphic overprint immediately following crust formation. This indicates that it has not been an integral part of Rodinia. The eastern boundary of the TOAST is probably in the vicinity of the Yamato Mts., whilst its northern extension might be seen in the Vohibori Terrane (SW Madagascar), which in turn could correlate with the Arabian Nubian Shield. The LN/EP tectono-metamorphic overprint of the TOAST shows a slight decrease in ages from W to E, possibly indicating that it first amalgamated on its Kalahari side before it was attached to Rukerland/Indo-Antarctica.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi